II Old English. Issue 1 (8th July 2020) - Burns, Rachel; Curran, Colleen; Hardie, Rebecca; Yang, Kaifan; Kehoe, Niamh; Knowles, Emma; Ponirakis, Eleni; Tedford, Margaret
Abstract: This chapter has eleven sections: 1. Bibliography; 2. Manuscript Studies, Palaeography, and Facsimiles; 3. Cultural and Intellectual Contexts; 4. Literature: General; 5. The Poems of the Exeter Book; 6. The Poems of the Vercelli Book; 7. The Poems of the Junius Manuscript; 8. Beowulf and the Beowulf Manuscript; 9. Other Poems; 10. Prose; 11. Reception. Sections 1, 9, and 11 are by Eleni Ponirakis; section 2 is by Rachel Burns and Colleen Curran, with contributions by Eleni Ponirakis; sections 3, 4, and 10 are by Margaret Tedford, with contributions from Eleni Ponirakis in section 3; section 5 is by Niamh Kehoe; section 6 is by Rebecca Hardie; section 7 is by Emma Knowles; section 8 is by Kaifan Yang.